Protein Digestibility and Protein Efficiency Ratio of Herbal Rice by Rats Given High Fat Diet - Fitri, Ahmad; Nurdin, Samsu Udayana; Sukohar, Asep; Subeki; Rizal, Samsul (JURNAL AGROINDUSTRI HALAL, 2023)
Herbal rice made from white rice by adding a mixture of turmeric, cinnamon and guava leaves during cooking, reducing cholesterol levels in hypercholesterolemia. This study was aims to evaluate the protein digestibility and protein efficiency ratio of herbal rice by rats given high fat diet. This study used 28 male Spangue dawley rats aged 12 weeks divided into four treatment groups (7 rats per group). The control group (P0) was given standard diet AIN-76 without high fat diet induction, the treatment group (P1) was containing plain rice flour with high fat diet induction, the treatment group (P2) was containing cooked rice flour 1 bag of mixed herbs with high fat diet induction, and the treatment group (P3) was containing cooked rice flour 2 bags of herbal mixture with high fat diet induction. The results showed that the body weight of each rat treatment group increased during the 28 days of the experiment. The type of ration given had a significant effect (p<0.05) on the value of protein digestibility, but had no significant effect (p<0.05) on the value of the protein efficiency ratio (PER). Result evaluation of body weight, protein digestibility and PER of herbal rice obtained, it can be concluded that herbal rice has better protein quality than plain white rice.